The Role of Student Digital Activism in Strengthening Ecological Citizenship and Environmental Health in Indonesia - Tarekh Febriana Putra; Agus Setiabudi; Hilman Gufron; Cahaya Juniarti; Syabill Qakfhan Mufthi Dharmawan (Lentera : Jurnal Kajian Bidang Pendidikan dan Pembelajaran, 2026)
The escalating environmental crisis requires higher education institutions to foster ecological citizenship through innovative forms of civic participation, including digital activism. However, empirical evidence on how students’ digital activism contributes to ecological citizenship and environmental health remains limited, particularly in vocational education. This study investigates the role of student digital activism in strengthening ecological citizenship and environmental health among polytechnic students in Indonesia. A mixed-methods sequential explanatory design was employed, with this article reporting quantitative descriptive-correlational findings. The study involved 71 students from diverse academic disciplines selected through purposive sampling. Data were collected using a 36-item Likert-scale questionnaire measuring digital activism, ecological citizenship, and environmental health perceptions. Descriptive analysis revealed an overall mean score of 3.467, indicating a moderate-to-high level. Pearson correlation analysis demonstrated a strong positive relationship between digital activism and ecological citizenship (r = .726, p < .001), while regression analysis showed that digital activism explained 52.7% of the variance in ecological citizenship (R² = .527). These findings suggest that meaningful digital activism is an effective pedagogical strategy for cultivating ecological citizenship and promoting environmental awareness. The study recommends integrating digital environmental activism into citizenship education curricula to strengthen civic engagement and sustainability competencies in vocational higher education.